PECULIARITIES OF ALIGNING THE NATIONAL AND EUROPEAN CRITERIA OF QUALITY ASSURANCE IN THE HIGHER EDUCATION SYSTEM OF THE RA (Education in the 21st Century, 2023)
The article presents the features of the Standards and Guidelines for Quality Assurance in theEuropean Higher Education Area (ESG), the alignment of the quality assurance standards of theRA with those of ESG 2015, as well as the problems of applying those standards in the highereducation system of the RA. To overcome the problems presented in the article, the need to reviewthe policies and strategies adopted at the state and institutional levels, especially the criteria andstandards for quality assurance of the Republic of Armenia, is emphasized while taking intoaccount the development taking place in the state and international educational spheres.